2014
DOI: 10.17660/actahortic.2014.1020.5
|View full text |Cite
|
Sign up to set email alerts
|

QTL Detection of Important Agronomic Traits for Sweet Cherry Breeding

Abstract: In the original publication, the numbers assigned to each haplotype in Fig. 2 and its expanded version (Supple-mentary Fig. S2) are not consistent with the numbers used in the article. The haplotype numbers are corrected and the haplotypes are reordered according to these new numbers in the attached revised Fig. 2 and Supplementary Fig. S2. Fig. 2 Marker allele composition of each haplotype across the five haploblocks for the sweet cherry QTL hotspot on chromosome 2 illustrated using the smallest number of mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
6
14
0
Order By: Relevance
“…Traits showing normal (MD) and bimodal (FD time) distribution were observed in this study, revealing different behavior of these traits. As reported here, normal distribution was previously observed for MD in sweet cherry 8 and apricot 5,27 . However, in most peach populations, bimodal distributions for MD were reported 10,11,25 .…”
Section: Haplotype Analysis Of Lg4supporting
confidence: 86%
See 1 more Smart Citation
“…Traits showing normal (MD) and bimodal (FD time) distribution were observed in this study, revealing different behavior of these traits. As reported here, normal distribution was previously observed for MD in sweet cherry 8 and apricot 5,27 . However, in most peach populations, bimodal distributions for MD were reported 10,11,25 .…”
Section: Haplotype Analysis Of Lg4supporting
confidence: 86%
“…Quantitative trait locus (QTL) analyses have been conducted in sweet cherry to investigate the genetic control of MD 7 9 but not FD period. Analysis of MD in a ‘Regina’ × ‘Lapins’ population during 3 years 7 , 8 identified three stable QTLs on linkage groups (LGs) 1, 4, and 5. A large percentage of variation was explained by a QTL on LG4 (20.4%), which was associated with advancing maturity 5.4 days 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This study is based on a model of individual SNP loci in linkage disequilibrium with chromosome segments containing numerous small-effect QTLs such that replication of SNP alleles across environments models the replication of causal alleles at the small-effect QTLs. However, as previous studies 10,12 have suggested the presence of large-effect QTLs contributing to genetic variation of fruit maturity timing, the model of genetic architecture used in this study might not be accurate. Incorporation of known QTL effects in the linear model should improve accuracy, as it is expected that such a model would more closely approximate the true distribution of QTL effects 77 .…”
Section: Discussionmentioning
confidence: 84%
“…Traditionally, sweet cherry cultivars are divided according to their maturity date into early (e.g., ‘Burlat’ and ‘Chelan’), mid- (e.g., ‘Bing’) and late season (e.g., ‘Sumtare’) 9 . Individual broad-sense heritability of fruit maturity timing is high (0.76–0.83) 10,11 and large-effect Quantiatative Trait Loci (QTLs) on linkage groups 1, 4, 5, and 6 have been detected within a full-sib family (‘Regina’ × ‘Lapins’), each explaining up to 20% of phenotypic variation 10,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Each genotype from the R×L progeny, grafted on 'Tabel Edabriz' rootstock, was planted in a large pot and placed in tunnels equipped with the overhead sprinklers. Slightly before maturity and irrigated during several hours at fixed times and for 5 d. Every day, the number of cracked fruits, out of a total of 100 fruits, was counted and removed (Quero-Garcia et al, 2009). This methodology was compared to cracking tolerance values observed in field conditions during three successive years (2008, 2009, and 2010).…”
Section: Genetics and Molecular Factors Involved In Fruit Crackingmentioning
confidence: 99%